School improvement and stakeholder response: Unpacking parental perceptions and interest - Siti Nafisah; Sunarto Sunarto; Nurul Asma Mazlan (At Turots: Jurnal Pendidikan Islam, 2025)
This study examines the interconnected effects of school improvement programs, parental perceptions, and parental interest in supporting educational development at MTs Sadamiyyah. Employing a quantitative design with a structured survey approach, data were gathered from 144 parents using a total sampling technique. Validated questionnaires captured responses, and the data were analyzed using multiple linear regression and path analysis. The results demonstrate that school improvement programs have a significant positive influence on parental perceptions (B = 0.45, p < 0.001) and parental interest (B = 0.28, p < 0.001). Moreover, parental perceptions notably mediate the relationship between school programs and parental interest (B = 0.53, p < 0.001), suggesting an indirect effect that strengthens parental engagement. High mean scores were reported for key indicators such as facility quality, teacher competence, and the availability of extracurricular activities. These findings underline the importance of parental perception as a strategic component in maximizing the effectiveness of school improvement initiatives. The study advocates for enhanced communication and engagement strategies between schools and parents to cultivate sustainable support and elevate educational quality. Future studies are encouraged to examine sociocultural and policy-related variables that may shape parental involvement in the school community.